The Novel Gabapentinoid Mirogabalin Prevents Upregulation of α2δ-1 Subunit of Voltage-Gated Calcium Channels in Spinal Dorsal Horn in a Rat Model of Spinal Nerve Ligation - Domon, Yuki; Kobayashi, Naoko; Kubota, Kazufumi; Kitano, Yutaka; Ueki, Hideaki; Shimojo, Yumiko; Ishikawa, Kayoko; Ofune, Yuka (Drug Research, 2022)
Gabapentinoids are specific ligands for the α2δ-1 subunit of voltage-gated calcium channels. This class of drugs, including gabapentin and pregabalin, exert various pharmacological effects and are widely used for the treatment of epilepsy, anxiety, and chronic pain. The mechanism of action of gabapentinoids involves both direct modulation of calcium channel kinetics and inhibition of channel trafficking and expression, which contribute to the above pharmacological effects. In the present study, we investigated the effects of mirogabalin, a novel potent gabapentinoid, on expression levels of the α2δ-1 subunit in the spinal dorsal horn in a rat model of spinal nerve ligation (SNL) as an experimental animal model for peripheral neuropathic pain. The neuropathic pain state was induced by SNL in male Sprague – Dawley rats. After the development of mechanical hypersensitivity, the animals received 10 mg/kg mirogabalin or vehicle orally for 5 consecutive days and were subjected to immunohistochemical analysis of α2δ-1 subunit expression in the spinal cord. In the SNL model rats, expression of the α2δ-1 subunit significantly increased in the spinal dorsal horn at the ipsilateral side of nerve injury, while mirogabalin inhibited this increase. In conclusion, the α2δ-1 subunit was upregulated in the spinal dorsal horn of SNL model rats, and repeated administration of mirogabalin inhibited this upregulation. The inhibitory effect of mirogabalin on upregulation of the α2δ-1 subunit after nerve injury is considered to contribute to its analgesic effects in peripheral neuropathic pain.
Keywords: analgesic; neuropathic; pain; trafficking; expression